2006
DOI: 10.1111/j.1754-4505.2006.tb01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the mandible in the aging population

Abstract: Maxillofacial trauma in elderly patients represents a significant social concern, as it uses one-third of all medical resources allocated to trauma care. Studies have shown the incidence of maxillofacial trauma in the elderly population has been increasing over the past 30 years. A common injury in patients who present with maxillofacial trauma is fracture of the mandible. The etiology, demographics, and management of elderly patients with mandibular fractures differ from younger cohorts. Falls are the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…Yamamoto et al. reported that maxillofacial fractures in elderly patients have been increasing in recent years and reached nearly 20% of all maxillofacial fractures in 2000 , which is considered to reflect the increased lifespan and number of elderly in the population, as well as their more active lifestyle as compared to previous generations . The male to female ratio in our study was 1: 1.1, which is similar to other studies , although in contrast to studies presented by Goldschmidt et al.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Yamamoto et al. reported that maxillofacial fractures in elderly patients have been increasing in recent years and reached nearly 20% of all maxillofacial fractures in 2000 , which is considered to reflect the increased lifespan and number of elderly in the population, as well as their more active lifestyle as compared to previous generations . The male to female ratio in our study was 1: 1.1, which is similar to other studies , although in contrast to studies presented by Goldschmidt et al.…”
Section: Discussionsupporting
confidence: 83%
“…Maxillofacial trauma has generally been shown to be more common in younger age groups, although the incidence is increasing in older individuals (1), which may be a reflection of increasing longevity and more active lifestyles among the elderly (2). The annual occurrence of injuries in older individuals has been reported to be as high as 29% (3), and substantial differences in response to trauma between older, young, and middle-age populations have been shown (2).…”
mentioning
confidence: 99%
“…2 As a consequence, they are increasingly exposed to risk of injury, 3 including injury to the head region. 4 The literature indicates that the prevalence of head injury among older populations in developed countries has increased over the last 30 years. 4 5 Given that the proportion of Australians aged 65+ years is projected to rise from 13% in 2002 to 27-30% in 2051, 6 head injuries in this age group are also likely to increase both in terms of case numbers and proportion of total injury.…”
mentioning
confidence: 99%
“…There has been debate on the treatment modalities for atrophic/edentulous mandibular fractures (19). In contrast, disruption of the blood supply by open reduction may lead to poor wound healing or nonunion of the fracture (3,10). In the present case, several factors were taken into account to choose the treatment modality.…”
Section: Discussionmentioning
confidence: 93%
“…Maxillofacial fractures in the elderly have been recently increasing as a consequence of their increased life span and more active lifestyle (1)(2)(3)(4). In the elderly, maxillofacial fractures often occur by falling, related to physiologic consequences of aging such as a reduced ability to balance and to avoid environmental hazards, the presence of systemic disease and the use of drugs (2,5).…”
mentioning
confidence: 99%